If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(u-8)-5=-5(-5u+4)-7u
We move all terms to the left:
3(u-8)-5-(-5(-5u+4)-7u)=0
We multiply parentheses
3u-(-5(-5u+4)-7u)-24-5=0
We calculate terms in parentheses: -(-5(-5u+4)-7u), so:We add all the numbers together, and all the variables
-5(-5u+4)-7u
We add all the numbers together, and all the variables
-7u-5(-5u+4)
We multiply parentheses
-7u+25u-20
We add all the numbers together, and all the variables
18u-20
Back to the equation:
-(18u-20)
3u-(18u-20)-29=0
We get rid of parentheses
3u-18u+20-29=0
We add all the numbers together, and all the variables
-15u-9=0
We move all terms containing u to the left, all other terms to the right
-15u=9
u=9/-15
u=-3/5
| 8x-7=-15 | | 3x-40=-19 | | Y2=2x-5 | | 9-x=82 | | 3(5x-4)-6=9x | | 2v+6=6v-10 | | 4m^2+41m+10=0 | | k-2/5=11) | | -7t=-8t+4 | | 7-5c=-6c | | 4c+9=3c | | 5x-8x+3x=0 | | 2x/3+4=1/6 | | {2×+9y=-14×+y=15} | | 5t2-20t-25=0 | | 4x^2-x-400=0 | | 185-r+341=288 | | -2x+2=3x+13 | | 3x^2-37x+336=0 | | 2x-2=2x+13 | | 20x²–15x–10=0 | | x/7.2+x/4.8=1 | | 910-n=297 | | 275=(6000-50x)/9 | | 91=c+26 | | 81x^2+72+16=0 | | k-5^1/4=4^5/6 | | 7x^2-7x+27=0 | | 8x^2+40x-72=0 | | -4*(2-x)=9 | | a÷32=2 | | 35x^2+13x-12=0 |